(untitled) (Research, Society and Development, 2022)
Aim: To identify and analyze, based on the reading of scientific evidence, what is currently being done to combat SAH, taking into account, from awareness and prevention, to care for patients who already have the disease. Methodology: An integrative review of the scientific literature carried out in February 2022, based on the survey carried out in the following data sources: ScienceDirect, SCOPUS, SciELO Brasil, VHL, LILACS, MEDLINE, Pubmed and Cochrane Library. The descriptors and Booleans used were: (Arterial Hypertension) AND (Prevention) AND (Care). Results and Discussion: Nine scientific articles were included in the study. It was found that the nursing intervention in the implementation of the most diverse means of communication and care for the hypertensive patient resulted in their greater adherence to specialized monitoring. Conclusion: From the study, it is observed the importance of health promotion, prevention and care of Arterial Hypertension (AH), in front of the nursing consultation, since this disease has a high prevalence and is one of the main risk factors for cardiovascular diseases (CVD), combined with environmental, social and genetic factors.